Cleaning Dusty Air Flow with a Rotary Cyclone from Dispersed Particles - Oleksandr Kravchenko; Oleksiy Bazhynov; Ján Dižo; Yevhen Haiek; Miroslav Blatnický (Communications)
The research presented in this article is aimed to show the prospective direction of increasing the efficiency of cleaning dusty air flows from light impurities and dust on mobile grain separators by using a rotary cyclone with a multi-disc after cleaner. An increase in the efficiency of the process of cleaning the dusty air flow in dust collectors is provided by an additional effect on dispersed particles for their intensive redistribution in the working areas. The developed rotary cyclone has two working zones: the main zone and the post-cleaning zone. The rotary cyclone consists of a bladed impeller, a main cylindrical channel, a sedimentation chamber and an after-cleaner. The overall air flow purification coefficient of the rotary cyclone varies between 87.5 to 92.5 %.